Time Machine: Experiencing time in the brain - Polydorou, Doros; Ben-Tal, Oded; Damsma, Atser; Schlichting, Nadine (My University, 2018)
Virtual Reality Experience presented at 4th International Conference on Time Perspectives.
Keywords: Virtual Reality; Time perspectives